Changes in clinical indicators in dogs with dilated cardiomyopathy - Zvenihorodska, T.; Shepel, K.; Dehnych, I. (Scientific Progress & Innovations, 2024)
Dilated cardiomyopathy (DCM) is one of the most common acquired heart diseases in both dogs and humans. It can manifest with pronounced symptoms or have a latent nature. Therefore, our aim was to investigate and assess the frequency of clinical indicators in dogs with dilated cardiomyopathy depending on the functional class of heart failure syndrome. Over the past year, 36 dogs were selected at the educational-scientific-production clinic of Poltava State Agrarian University and divided into groups according to the functional class of heart failure, based on the modified scheme available on the New York Heart Association’s website. The study evaluated the clinical manifestations of dilated cardiomyopathy in dogs with different functional classes of heart failure. The research utilized an Aloka F 37 ultrasound machine with a sector ultrasound probe and a base scanning frequency of 5 MHz, as well as an Arman 9L5 X-ray machine. The signs of dilated cardiomyopathy included a body weight- normalized left ventricular end-diastolic dimension > 1.7 units and a normalized left ventricular end-systolic dimension > 1.0 units, as well as a left ventricular ejection fraction < 45%. The asymptomatic course of dilated cardiomyopathy in dogs of various breeds was also manifested by the presence of persistent atrial fibrillation, supraventricular tachycardia, and ventricular arrhythmias. Radiographic signs of dilated cardiomyopathy included an enlarged left ventricular and atrial silhouette, with a vertebral heart score (VHS) > 11. To compare two groups, the non-parametric Mann-Whitney U-test was used, and for comparing multiple groups, the Kruskal-Wallis test was applied. The non-parametric χ² test was used to compare the frequency of qualitative characteristics between groups. The relationship between the functional class of heart failure syndrome and clinical indicators was determined using Spearman’s correlation method. The difference between the study groups of dogs was considered significant at P<0.05. A statistically significant increase in capillary refill time (P<0.05 and P<0.001 in dogs of III and IV functional classes) and a decrease in body temperature (P<0.001 in dogs of IV functional class) were observed. An increase in heart rate was detected at 1.1, 1.4, and 1.7 times during examination and 1.3, 1.6, and 2.5 times at rest, respectively, compared to clinically healthy animals, with tachypnea showing a positive correlation with disease severity. Peripheral edema and ascites were recorded less frequently, but their incidence increased in later classes. Dyspnea appeared as an early symptom of the pathology. Cyanosis of the mucous membranes and diffuse cardiac impulse were noted in dogs of III and IV functional classes of heart failure. An increasing frequency of systolic murmur, dependent on the stage of the disease, was detected. The frequency of dry cough increased in dogs with heart failure of II-IV functional classes (50, 66.7, and 66.7, respectively). The results emphasize the necessity of early diagnosis for effective treatment of cardiomyopathy in dogs.